Pengaruh ULLTT terhadap Penurunan Nyeri terhadap Kasus HNP Cervical - Lilik Sigit Wibisono; Syurrahmi Syurrahmi; Widya Ervianta; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Background: Hernia Nucleus Pulposus (HNP) is a condition when the pad or disc (soft gel disc or nucleus pulposus) between the vertebrae (spine) comes out of its original position or is torn and pinches the nerve behind it. Many people know it as "pinched nerve". HNP most often occurs in the cervical (neck) and lumbar (waist) vertebrae. The neck has 7 vertebrae. Cervical HNP (pinched neck nerve) most often affects the C6-C7 segment followed by the C5-6 segment because this segment is the part that moves most often and is easily affected by the degeneration process. Neck HNP most often occurs in men aged 45-55 years. Risk factors that increase the appearance of cervical HNP or pinched neck nerves include genetics, smoking, being overweight (obesity), work that often involves bending over and lifting heavy objects or operating machines with vibrating forces, and injury. Nerve mobilization in the Upper Limb Tension Test ( ULTT) is performed on branches of the Brachial plexus such as the radial nerve, median nerve and ulnar nerve. But here the author only discusses ULTT on the median nerve, namely ULTT 1 which is related to CTS. The aim is to determine physiotherapy management and the effect of Ultrasoundtherapy therapy and nerve mobilization using the ULTT 1 method in cases of Carpal Tunnel Syndrome on reducing pain and increasing the functional ability of the hand. Two group pre test and post test method. RESEARCH PLACE: Physiotherapy clinic, RSU Sidoarjo. TIME: Measuring instrument: Visual Analouge Scale (VAS). Results: treatment using the Mann-Whtney test. With confidence interval (CI) (95%) The results of the study revealed that there was a significant difference in pain in group 1 (p = 0.00) and group 2 (p = 0.00). But there was no significant difference between the two groups in pain improvement (p = 0.152), so there was no better treatment between the two groups. Conclusion: It is concluded that ULTT is useful in treating cervical HNP patients to reduce pain in two groups. The targeted outcomes are publications in national journals indexed by Sinta and HAKI. The TKT target for implementing this gamelan accompaniment exercise is level 2.